Quantifying Damage Evolution in Fiber-reinforced Composites Using Fracture Mechanics - Amit Shishodia (International Journal of Fracture Mechanics and Damage Science, 2024)
By evaluating the evolution of damage, such as cracks or delamination, within the material over time or under various loading situations, damage evolution in fiber-reinforced composites can be characterized using fracture mechanics. Fracture mechanics offers a framework for understanding and projecting the behavior of materials that already have damage or flaws. Since they have a high strength-to-weight ratio and unique mechanical qualities, fiber-reinforced composites are essential in many branches of engineering. In order to guarantee structural integrity and dependability, it is essential to comprehend and measure the evolution of harm within these materials. This study uses fracture mechanics to give an exhaustive look into how to quantify damage evolution in composites made from fiber-reinforced materials. To collect data on fracture the beginning, propagation, and total damage progression, the study combines mathematical simulations, experimental testing, and scientific modeling.
Keywords: Fiber-reinforced composites; damage evolution; fracture mechanics; propagation; strain energy